AMAP Strategic Framework 2019+ - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2019)
The Arctic is experiencing unprecedented change, including climate change, due to human activities within and outside the region. These changes are complex and are attracting global attention, resulting in a growing need for useful, timely and targeted information in order to make effective decisions and mitigate risks to people, governments, businesses and the environment. Looking ahead, the demand for reliable and accessible data and information will continue to grow. AMAP has a unique role in documenting and understanding Arctic change, predicting the future, assessing impacts, and informing Arctic and global communities by providing comprehensive, credible information and clear, direct science-based recommendations to protect the Arctic environment, its ecosystems and humans, as well as to mitigate threats and enhance sustainable development of the Arctic.